Analisis Representasi Kenangan Masa Kecil Dalam Seni Lukis Dekoratif Karya Seni Lukis Amrina Rosada - Lalu Aswandi Mahroni G (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
This article discusses the representation of Amrina Rosada’s childhood memories through painting using an illustrative decorative style. The rapid development of digital technology has changed children’s play patterns and social interactions from direct physical activities to screen-based activities. This condition encourages reflection on childhood values that are gradually diminishing. This study employs an art creation method with a qualitative exploratory–reflective approach, including personal memory exploration, social observation, painting technique experimentation, and visual design.The results consist of four acrylic paintings on canvas, namely Playing Five Stones, Bathing in the River, Collecting Frangipani Flowers, and Cycling with Friends. These works represent childhood experiences that emphasize togetherness, social interaction, freedom of play, and closeness to nature. Visually, the paintings apply simplified forms, narrative compositions, and warm pastel colors to create a nostalgic atmosphere.The findings indicate that the illustrative decorative style is effective in transforming personal memories into a communicative visual language. In this study, painting functions not only as an aesthetic expression but also as a reflective medium to reintroduce childhood values that remain relevant in contemporary social life.